Optimized Ferromagnetic Core Magnetorquer Design and Testing for LEO Nanosatellite Attitude Control - Villalba-Alumbreros, Gabriel; Lopez-Pascual, Diego; Diez-Jimenez, Efren (Applied Computational Electromagnetics Society Journal (ACES), 2024)
Magnetorquers are a very suitable solution for the nanosatellite’s attitude and orbital control of low Earth orbit (LEO) given its constraints: small available volume, limited power consumption, and maximum weight limitation. In this work, an optimized ferromagnetic core magnetorquer is designed for LEO nanosatellites, considering the geometrical, electrical, and magnetic parameters in an electromagnetic finite element analysis (FEA). The final design dimensions are 10.9 mm diameter and 100 mm in length, with a ferromagnetic core made of high performance soft magnetic alloy Vacoflux50 measuring 5 mm diameter and 100 mm in length. Magnetorquer geometry has been optimized to achieve a very high compactness, reaching an optimal combination of high specific magnetic moment and magnetic moment-input power ratio at the same time. It shows a maximum magnetic moment of 1.42 Am2, a magnetic moment-input power ratio of 2.52 Am2/W, and a specific magnetic moment of 22.5 Am2/kg, with a power consumption of 0.565 W and 0.5 A. Such a combination of high-performance values has not been previously found. Furthermore, it has displayed higher magnetic moment and specific magnetic moment than previous prototypes in literature. The simulated model is validated with the experimental testing of a manufactured prototype, by measuring the magnetic and electric variables.